Editor’s Note - Julie Balch Samora (Journal of the Pediatric Orthopaedic Society of North America, 2023)
The current composition of the pediatric orthopaedic workforce does not reflect the U.S. population. However, a diverse workforce can improve productivity, innovation, communication, patient satisfaction, equitable care, and can increase care for the underserved, reduce health disparities, and ultimately enhance overall population health. In this supplement, issues surrounding diversity, equity, and inclusion will be reviewed. Diversity can relate to race/ethnicity, gender, age, socioeconomic status, sexual orientation, disability, work experience, and political beliefs. Equity refers to fairness and justice focusing on outcomes, keeping in mind that everyone faces different challenges and has unique needs. Inclusion involves authentic and empowered participation, with a true sense of belonging and full access to opportunities. The objectives for this supplement include expanding readers’ existing knowledge to be able to: 1) enhance the learning and work environment and improve patient outcomes by cultivating diversity, equity, and inclusion; 2) assess and appreciate individual implicit biases and develop tools to minimize unconscious biases when working with others, training young surgeons, and caring for patients; and 3) develop skills to address unique needs and considerations of individuals in non-majority populations. I would like to express my gratitude to Mininder Kocher, MD, who enthusiastically supported this Pre-Course, and to Ken Noonan, MD, who graciously agreed to publish these discussions in JPOSNA®. I would like to thank each of the authors for summarizing the literature in their distinct areas and for sharing their words of wisdom. And of course, none of this would be possible without Lisa DuShane’s constant beating of the drum, moving us toward the finish line. I hope you enjoy this rich compilation of data, anecdotes, and suggestions to make our pediatric orthopaedic environment an open, inclusive, and supportive place to work, learn, and heal.